PROBLEMS OF IMPLEMENTATION IN RUSSIAN STATE ACHIEVED BY PROVIDING EDUCATIONAL SERVICES FOR HIGHER EDUCATION PROGRAMME - Larisa Alexandrovna Krokhmal (Модернизация, инновация, развитие, 2016)
For a long time, university funding was based on individual standards, taking into account only the volume of financial support prior periods for a particular university. In 2010, radical changes in the activities of universities introduced the Federal Law on changing the status of public institutions, which radically changed the conditions of functioning of universities and suggested that new tools of state regulation. The leading and recognized, a tool in the organization of financing of Russian institutions of higher education today is a state task for the implementation of educational services. For the universities the amount of the provision of public education services is determined by the Russian Ministry of Education enrollment by calculating the average annual contingent with the expected acceptance and release. The state has become a defining task of university development tool on the amount of which depends on the economic well-being of the university. On financial support for implementation of the state task universities are subsidized from the respective budget. Using state task, the executive authorities and evaluate the qualitative characteristics of services to be implemented by universities. There is no doubt that the state assignment for the provision of educational services contributes to the functioning of universities to stimulate the search for new areas of training, as well as the diversification of funding sources. At the same time, a new and still not adapted to the conditions of functioning of universities tool, which the study will create the best conditions for university activities. The practice of arranging financing based on the state task for the implementation of educational services contains a number of contradictions that have a negative impact on the activities of the universities, and complicate the process of adaptation to the new requirements. The article discusses the contradictions that arise in the organization about bringing the state task universities and assessment of qualitative characteristics of educational services.